MODERNISME ISLAM DALAM BIDANG MANAJEMEN BISNIS SYARIAH - Muhaimin, Kharisma; Yuliatul Wahidah, Evita; Amany, Amany (Al-Idarah, 2024)
Modernism in Islam in the Field of Shariah Business Management. Modernism in Islam in the field of Shariah business management focuses on building a business management system based on Islamic values. In practice, Shariah business management must be grounded in spiritual values, understand what constitutes halal and haram business, and focus on both worldly and eternal outcomes, rather than solely on the compatibility of theory with practice. The progress of Islam in the fields of economics and business is inseparable from technological advancements and the development of time. The role of Islamic business ethics and good human resources also significantly influences modernism in Shariah business management. This study is conducted through a literature review, collecting and analyzing written sources such as books, journals, articles, and theses. The purpose of this journal is to understand the processes of Islamic modernization in Shariah business management and the impact of technological advancements on the development of Shariah business. In essence, modernism in Islam in Shariah business management aims to create a business management system that is grounded in Islamic values and oriented towards eternal happiness, while maintaining social responsibility and moral values.